Alzheimer’s Disease in Dentistry: Repercussions and management in oral health - Lupp, Juliana dos Santos; Silva, Luis Augusto de Almeida; Gomes, Julia de Cassia Borato; Marques, Thays Oliveira; Freitas, Fernanda Martins de Godoy; Silva, Leonardo Alvares Sobral (Seven Editora, 2023)
Alzheimer’s disease is one of the most prevalent forms of neurodegenerative dementia that mainly affects elderly individuals, manifesting itself through cognitive disorders that include gradual memory loss, communication difficulties and temporal and spatial disorientation. So far, the etiology of this disease remains uncertain, and its most challenging feature is the lack of a definitive cure, which makes treatment focused on delaying its progression and controlling symptoms. To achieve these goals, it is essential to adopt a multidisciplinary approach involving physicians, nurses, physiotherapists and dentists. The purpose of this work is to present the fundamental principles related to Alzheimer’s disease, as well as its implications for oral health, offering guidance to dental professionals on how to conduct care for these patients. The dental surgeon assumes a crucial role in guiding and instructing the patient’s caregivers and family members, in order to guarantee the maintenance of the oral health of these individuals. In addition, the professional must plan a treatment that prioritizes adequacy, prevention and promotion of oral health, seeking to provide greater comfort and well-being and, therefore, improving the quality of life of patients with Alzheimer’s. DOI:https://doi.org/10.56238/globalhealthprespesc-059